Indonesia's International Economic Strategies - Verico, Kiki. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book discusses Indonesia's international economic strategies. It examines unilateral aspects, foreign direct investments, bilateral economic relations, regional elements, ASEAN's role, and the Indo-Pacific's dynamic frameworks. Starting at the unilateral level, the book outlines how Indonesia managed its macro-economy to recover quickly and adequately from 2020 to 2021 amidst the global COVID-19 pandemic. It argues that Indonesia needs an open economic principle to enhance trade and investment relations. In addition, the book elaborates on how Indonesia transforms its economy with export-oriented long-run investment (Foreign Direct Investment) inflows as a necessary condition for economic transformation as it fits with Indonesia's manufacturing sector, which is critical to the country. Further, the book thoroughly explains Indonesia's bilateral economic relations, from its production networks with Indonesia's major partners to their impacts. It highlights the products which will provide enormous potential benefits for the country. The book also covers regional and mega-regional aspects of Indonesia's economy. Focusing on the Association of Southeast Asian Nations (ASEAN), it emphasises the regional organisation's three essential principles for economic integration: openness, convergence, and inclusiveness. In doing so, research in the book also includes perspectives on how ASEAN sees Asia and the Indo-Pacific framework. It also argues that ASEAN needs centrality in enlarging its economic cooperation with other countries or regions and how a member state's unilateral and bilateral liberalisation are building blocks for ASEAN. Kiki Verico is the author of The Future of The ASEAN Economic Integration (Palgrave Macmillan, 2017), which explores open regionalism as the necessary condition of the ASEAN economic transformation. Kiki is a tenure track professor in International Economics at the Faculty of Economics & Business University of Indonesia (FEB UI) and a Senior Researcher of the LPEM UI. He has been working as a lecturer and researcher for more than 20 years. He dedicates himself to teaching and doing collaborative research with government institutions, international organizations, business associations, and many others. Since his appointment in January 2020, he has served as a Senior Advisor for Industry and International Trade to Indonesia's Finance Minister.
Chapter 1: General Introduction -- Chapter 2: Global pandemic's scarring effects and Indonesia's economy -- Chapter 3: Economic Openness for Economic Transformation -- Chapter 4: Analysing Indonesia's bilateral trade and investment network -- Chapter 5: Analysing bilateral Comprehensive Economic Partnership Agreement (CEPA) Impacts -- Chapter 6: Optimizing benefit of bilateral CEPA: Indonesia with Australia and Republic of Korea -- Chapter 7: ASEAN Economic Integration Principles: Open, Inclusive and Convergence -- Chapter 8: Keeping Indo-Pacific peace and prosperous -- Chapter 9: Choosing the right mega-regional economic cooperation -- Chapter 10: General Conclusion.
Keywords: International economic relations; International law; Trade regulation; International trade; Asia -- Economic conditions; International Economics; International Economic Law, Trade Law; International Trade; Asian Economics